q(2+3q)-q(5q-7)=

Simple and best practice solution for q(2+3q)-q(5q-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for q(2+3q)-q(5q-7)= equation:


Simplifying
q(2 + 3q) + -1q(5q + -7) = 0
(2 * q + 3q * q) + -1q(5q + -7) = 0
(2q + 3q2) + -1q(5q + -7) = 0

Reorder the terms:
2q + 3q2 + -1q(-7 + 5q) = 0
2q + 3q2 + (-7 * -1q + 5q * -1q) = 0
2q + 3q2 + (7q + -5q2) = 0

Reorder the terms:
2q + 7q + 3q2 + -5q2 = 0

Combine like terms: 2q + 7q = 9q
9q + 3q2 + -5q2 = 0

Combine like terms: 3q2 + -5q2 = -2q2
9q + -2q2 = 0

Solving
9q + -2q2 = 0

Solving for variable 'q'.

Factor out the Greatest Common Factor (GCF), 'q'.
q(9 + -2q) = 0

Subproblem 1

Set the factor 'q' equal to zero and attempt to solve: Simplifying q = 0 Solving q = 0 Move all terms containing q to the left, all other terms to the right. Simplifying q = 0

Subproblem 2

Set the factor '(9 + -2q)' equal to zero and attempt to solve: Simplifying 9 + -2q = 0 Solving 9 + -2q = 0 Move all terms containing q to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -2q = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -2q = 0 + -9 -2q = 0 + -9 Combine like terms: 0 + -9 = -9 -2q = -9 Divide each side by '-2'. q = 4.5 Simplifying q = 4.5

Solution

q = {0, 4.5}

See similar equations:

| 0.15x+0.05(4-x)=0.10(12) | | .25(.9x)=nx | | 4(s+3)-1=3x-5 | | 21/4x-1/2 | | -3(1-9z)-(-11z-11)= | | 3(-7-2x)+6(3x-7)=-51 | | 2x-6x+3x= | | 34=-2(2p+5)+5(1-7p) | | X=1.75+1.75X | | 3(t+7)-4=17 | | -4n-4(n-1)=12 | | 5=1+n-2 | | 5x^3+14x^2-3x=0 | | -(1-6x)-5=12 | | (a^4*-ac)+(c^3*d^2)= | | 5/7x15 | | 15x+25y=1400 | | c/5-c-1/10=9/10 | | 5X+7-2x=-11 | | 2y-10x=70 | | 17=3t+5 | | 5x-3y+2x+y= | | 6=3s-3 | | 3.12-d+2.1=1.910 | | (8+7i)-(-2+3i)= | | c-2.2+7.35=9.2 | | 2x+81=99 | | B-4.14=2.13-1.14 | | (X^2)-(0.5x)-(0.6)=0 | | -6+n=-2n | | C-2.2+7.35=9.3 | | x3=27/64 |

Equations solver categories